Hematocolpos as a Result of Delayed Treatment of Acute Straddle Injury in an Adolescent Girl - Hae Jin Hwang; Hyun Wook Lim; Young Shin Han; Jeong In Choi; Min Jeong Kim (Hindawi Limited, 2016)
Accidental genital trauma is most commonly caused by straddle-type injuries and is usually treatable by nonoperative management, and most of the injuries have a good prognosis. When the bleeding occurred due to straddle injury in adolescent girl, experienced gynecological examination and treatment were very important. We experienced a case of straddle injury to the posterior fourchette that caused acute hematocolpos due to delayed adequate treatment with hypotension and acute abdomen in an adolescent girl. This case shows the importance of careful and accurate physical and gynecological examination and adequate and prompt treatment of genital trauma in adolescent girls.